The Role of Institutional Ownership in Detecting Fraudulent Financial Reporting: Fraud Heptagon Model Analysis - Devina Putri Indra Satata; Imang Dapit Pamungkas; Anna Sumaryati; Bambang Minarso (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study investigates the impact of seven factors: pressure, opportunity, rationalization, capability, arrogance, ignorance, and greed on Fraudulent Financial Reporting using the Fraud Heptagon model analysis, with Institutional Ownership and the Audit Committee as moderating variables. Focused on state-owned enterprises in Indonesia from 2018 to 2022, purposive sampling yielded 141 samples. Employing regression analysis through Warp PLS software version 8.0, results indicate that opportunity, capability, and ignorance negatively affect fraudulent financial reporting, suggesting potential mitigating roles. Conversely, pressure, rationalization, arrogance, and avarice positively impact Fraudulent Financial Reporting. Notably, institutional ownership moderates the correlation between Greed on fraudulent financial reporting. These findings contribute insight into the dynamics of Fraudulent Financial Reporting activity, emphasizing the need for a comprehensive understanding and strong control mechanisms to effectively prevent Fraudulent Financial Reporting.